Pengaruh Financial Capabilities, Networking Terhadap Kinerja Usaha UMKM di Kota Sukabumi Melalui Intellectual Capital - Samuel P.D. Anantadjaya; Irma M. Nawangwulan; Eki Candra; Rahmatya Widyaswati; Achmad Choerudin (Universitas Nusa Putra, 2023)
This study aims to investigate the influence of financial capability, networking, and intellectual capital on the business performance of micro, small, and medium enterprises (UMKM) in Sukabumi City. The research adopts a quantitative approach and is analyzed using SEM-SmartPLS version 4. The sample consists of 140 UMKM in Sukabumi City selected through quota sampling. The research findings demonstrate that financial capability and networking have a significant positive impact on UMKM business performance, and intellectual capital partially mediates this relationship. This study has several implications for policymakers, UMKM owners/managers, financial institutions, and business associations in Sukabumi City.